Islam dan Moderasi Beragama - Adnan Sulaiman; Adnin Abdul Majied; Alya Huriah Assegaff; Anida Farroh; Asep Abdul Muhyi (Gunung Djati Conference Series, 2023)
This study examines Islam and religious moderation which is one of the contemporary issues in the perspective of the Qur'an. With the muadhu'i interpretation method, namely by presenting the verse, its translation, Asbabun nuzul, munasabah, and interpretation. Starting with choosing the equivalent of words that have to do with the word moderation in the Qur'an then quoted and elaborated with the method of tafsir maudhu'i. This study concludes that in Islamic thought and the perspective of the Qur'an, moderation encourages tolerance of differences. willingness to embrace diversity (inclusivism). Diversity in madhhabs and also religious diversity. Our differences do not prevent us from working together under the basic idea of humanity. Thinking that Islam is the true religion does not require us to harass followers of other religions, so that there is religious harmony and unity. Nowadays, moderation generally refers to the balance between creed, behavior, relationships between people, and morals, showing that Islam is a moderate religion that does not have extreme beliefs, arrogance, gentleness, and other traits. To show religious moderation can be shown by cultivating the values contained in various moserasi in daily life such as taking the middle path (tawassuth), balance (Tawazun), Tolerance, deliberation, reform, dynamic and innovative and civilized.